2018
DOI: 10.1007/s11934-018-0763-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Genitourinary Microbiome in Pediatric Urology: a Review

Abstract: Purpose of Review In this review, we highlight the effects of the microbiome on urologic diseases that affect the pediatric patient. Recent Findings Perturbations in the urinary microbiome have been shown to be associated with a number of urologic diseases affecting children, namely urinary tract infection, overactive bladder/urge urinary incontinence, and urolithiasis. Summary Recently, improved cultivation and sequencing technologies have allowed for the discovery of a significant and diverse microbiome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…The UT microbiota represents 21.4% of the known prokaryotic diversity associated with humans and 62.3% of organisms identified in urine can also be found in the human gut microbiota [263]. As has been observed for the gut microbiome [239,243,244], current evidence suggests that microbiota profiles play significant roles in UT disease occurrence and progression [223,[264][265][266][267][268], but extensive additional studies are needed to further elucidate complex host-microbiota interactions within the UT using methods and perspectives that have been applied to other microbiome studies [222,241,242,246]. The presence of soluble, plant-derived, dietary oligosaccharides in urine would be significant in terms of UT health, through both prebiotic effects on UT microbiota and direct biological and chemical effects, and the possible influence of these compounds must be considered in the context of both cranberry and other dietary sources.…”
Section: Cranberry Carbohydrates and Human Microbiotamentioning
confidence: 88%
“…The UT microbiota represents 21.4% of the known prokaryotic diversity associated with humans and 62.3% of organisms identified in urine can also be found in the human gut microbiota [263]. As has been observed for the gut microbiome [239,243,244], current evidence suggests that microbiota profiles play significant roles in UT disease occurrence and progression [223,[264][265][266][267][268], but extensive additional studies are needed to further elucidate complex host-microbiota interactions within the UT using methods and perspectives that have been applied to other microbiome studies [222,241,242,246]. The presence of soluble, plant-derived, dietary oligosaccharides in urine would be significant in terms of UT health, through both prebiotic effects on UT microbiota and direct biological and chemical effects, and the possible influence of these compounds must be considered in the context of both cranberry and other dietary sources.…”
Section: Cranberry Carbohydrates and Human Microbiotamentioning
confidence: 88%
“…Future studies will also have to address the influence of diet/nutrition on the bladder microbiome. Regarding the function of the urinary tract, colonization with various bacteria such as Corynebacterium, Oligella, Staphylococcus, and Actinomyces has been shown to be associated with urge urinary incontinence [6]. As there are presently no data regarding associations between the microbiome and the function of the urinary tract in patients after bladder augmentation, this issue will have to be addressed in future prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing (NGS) techniques have provided novel insights into the microbiome of the urinary bladder (UB) [4], which until now has been suspected to be sterile [5]. However, there is a growing body of evidence suggesting that even the healthy urinary tract harbors a variety of microbial species, termed the urinary microbiome [6]. Furthermore, disruptions of the microbiome of the UB have been demonstrated in urological disorders such as urgency urinary incontinence, overactive bladder, and urolithiasis [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dogma regarding the sterility of urine was recently challenged with the identification of the urinary microbiome. [43][44][45] Since its initial description, a number of studies have shown decreased microbial diversity in the setting of an UTI, suggesting a potential role of the urinary microbiome in UTI pathogenesis. [46][47][48] These studies that propose a role of the urinary microbiome in UTI pathogenesis are supported by older in vitro work.…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%